Advanced Imaging Techniques in Diagnosis of Posterior Reversible Encephalopathy Syndrome (PRES) - Sheikh-Bahaei, Nasim; Acharya, Jay; Rajamohan, Anandh; Kim, Paul E. (Frontiers in Neurology, 2020)
Diagnosis of Posterior Reversible Encephalopathy Syndrome (PRES) in some circumstances can be challenging and structural imaging may not be sufficient to distinguish it from other differential diagnostic considerations. Advanced imaging techniques such as MR spectroscopy or positron emission tomography (PET) can provide additional information to determine the diagnosis. Other techniques such as susceptibility weighted imaging (SWI) improves detection of hemorrhage which has prognostic role. CT or MR Perfusion as well as Single-Photon Emission Computed Tomography (SPECT) are more useful to understand the underlying vasculopathic changes in PRES and may answer some of the unresolved controversies in pathophysiology of this complex disease. In this review we summarized the findings of previous studies using these advanced methods and their utilities in diagnosis or prognosis of PRES.